Willingness to pay for social health insurance among public civil servants: A cross-sectional study in Dessie City Administration, North-East Ethiopia - Amilaku, Eshetie Meseret; Fentaye, Fasil Walelign; Mekonen, Asnakew Molla; Bayked, Ewunetie Mekashaw (Frontiers in Public Health, 2022)
Background: The readiness to pay for health insurance has an impact on universal health care. This study investigated the willingness of public civil servants in Dessie city administration, North-East Ethiopia, to pay for social health insurance and associated factors. Methods: From April to May 2021, a cross-sectional study was undertaken. The sectors from which the samples were proportionately allocated were chosen using a multistage sampling procedure. Using their payroll list as a sampling frame, simple random sampling was done to recruit them. A semi-structured self-administered questionnaire was used to collect data. Epi Data version 3.1 was used to enter, code, and clean the data, which was then exported to SPSS version 23 for analysis. To determine relationships, bivariable and multivariable analyses were utilized. Candidates for multivariable analysis were variables with a p-value ≤ 0.3 in bivariable analysis. AOR with a 95% CI was used to determine the strength and direction of association. Statistical significance was defined at p-value < 0.05. Results: A total of 796 employees took part in the study, with a 94.42% response rate. Overall, 29.9% of them were willing to pay for the scheme (95% CI: 26.4, 33%). The decision to pay was influenced by favorable perception (AOR = 2.43, 95% CI: 1.72, 3.44), household income less than Birr 5000 (AOR = 0.26, 95% CI: 0.14, 0.48), acute illness (AOR = 0.48, 95% CI: 0.32, 0.72), bachelor level education (AOR = 0.44, 95% CI: 0.28, 0.70), master and above level education (AOR = 0.26, 95% CI: 0.14, 0.49), and age 25 to 29 years (AOR = 1.97, 95 % CI: 1.08, 3.57). Conclusion: The willingness of the civil servants to pay for social health insurance was low, and it was influenced by their attitudes toward the scheme, the occurrence of severe illness, income level, educational status, and age.